Aesthetic and World Politics by Roland Bleiker. Basingtoke, Hampshire: Palgrave Macmillan, 2009. Hardcover: 271 pp. - Siti Aliyuna Pratisti; Junita Budi Rachman (Intermestic: Journal of International Studies, 2017)
Aesthetic approach to politics is not really something considered as a novelty. Immanuel Kant has described the aesthetic relationship with rationality way back in the 17th century, as well as Friedrich Nietzsche and Jaques Rancier as a more contemporary counterpart. In the field of international relations, the study of aesthetics has been raised by a number of reviewers â€“ from James Der Derian, Costas Constantinou, David Campbell, to Anthony Burke â€“ who began to lay aesthetics as a foothold in approaching various phenomena. Roland Bleiker is one of the most consistent among them. In an essay entitled "The Aesthetic Turn in International Political Theory", Bleiker opened the discourse to establish aesthetics as one of the paradigms in international political theory. His essay is published in 2001, contrasts with the majority of international political theories that always try to "catch the world as it is". Bleiker assumes that there is always a distance between representation and what it represents. Through aesthetics, he criticizes approaches that fill this theoretical gap with mimetic ideas. He emphasizes that aesthetic studies do not try to mimic the reality, but it is trying to recognize the various emotions and sensibilities in the formation of a certain representation. The great role of "emotion" in politics is further explained by Bleiker through an essay entitled â€œFear No More: Emotions and World Politicsâ€, published seven years after.